Buscando un lugar en la nación : el camino de una Asociación de Autoridades Tradicionales Indígenas amazónica en la búsqueda de reconocimiento dentro del régimen multicultural colombiano (2020)
This work explores the different forms that the Colombian multicultural regime takes in a range of actors between institutions, indigenous people and NGOs in the Vaupés department in the Colombian Amazon.